Nutritional Status, Physical Activity, Sugar Consumption and The Risk of Diabetes Mellitus in Samarinda - Pangestu, Leni Setya; Siswanto; Naim, Tanti Asrianti (Miracle Journal of Public Health, 2024)
Type 2 Diabetes mellitus is a chronic disease that has experienced an increase in recent decades. The prevalence of type 2 diabetes in Indonesia increased from 10.9% in 2013 to 10.9% in 2018. Puskesmas Sidomulyo ranked first in the highest incidence of diabetes mellitus in Samarinda, with 2,041 cases in 2021. This study aimed to determine the risk of type 2 diabetes mellitus based on nutritional status, physical activity, and sugar consumption in diabetes mellitus patients in Sidomulyo Community Health Center. This was an observational study with a case-control design. The number of samples was 472, with a cases and controls ratio of 1:1. From 236 diabetes mellitus patients, most of the patients were female (72%), and the majority were aged ≥45 years old (65,1%). From this research results, it was found that nutritional status (OR=1,551; 95%CI=1,046-2,299), physical activity (OR=2,532; 95%CI=1,221-5,253), and sugar consumption (OR=7,130; 95%CI= 4,735-10,736) are the risk factors of type 2 diabetes mellitus at the Sidomulyo Community Health Center, Samarinda. The community is expected to increase prevention efforts through a healthy lifestyle, early detection, and diabetes management, especially in high-risk groups.